2009
DOI: 10.2134/jeq2008.0417
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐facilitated Pesticide Leaching from Differently Structured Soil Monoliths

Abstract: The leaching of soil particles and surface applied 14C-labeled glyphosate and pendimethalin from intact soil columns (height: 50 cm; diameter: 30 cm) were investigated, and the relative significance of particle-facilitated pesticide transport was quantified. Investigations were performed with a recently plowed (four columns) and an untilled (five columns) sandy loam soil. Leaching was driven by three irrigation events (15 mm h(-1); 2 h each). Samples of the leachate were filtered immediately (within 1.5 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 30 publications
1
47
1
2
Order By: Relevance
“…Leaching in field conditions have been reported before (Kjaer et al, 2011;Gjettermann et al, 2009). After glyphosate application in the field, the presence of the herbicide is limited to the surface layer of the soil, favoring the association between soil particles.…”
Section: Texture (%)mentioning
confidence: 64%
See 3 more Smart Citations
“…Leaching in field conditions have been reported before (Kjaer et al, 2011;Gjettermann et al, 2009). After glyphosate application in the field, the presence of the herbicide is limited to the surface layer of the soil, favoring the association between soil particles.…”
Section: Texture (%)mentioning
confidence: 64%
“…Gjettermann et al (2009) had a maximum recovery in the leached samples of 0.32% from the initially applied glyphosate. They found that 68% of the leached glyphosate was bound to the soil particles (N20 nm), suggesting that particle-facilitated transport is an important process involved in glyphosate transport.…”
Section: Texture (%)mentioning
confidence: 94%
See 2 more Smart Citations
“…6 and Table 2 lead to the conclusion that preferential flow was more pronounced at the Silstrup site, leading to higher susceptibility to leaching of agrochemicals and colloids (Norgaard et al, 2012). As demonstrated in numerous studies (e.g., Petersen et al, 1997;Gjettermann et al, 2009;Ersahin et al, 2002), pore geometry and macropore features are highly affected by soil management. Presumably, the period without tillage (almost 2 years) at Silstrup ) and significant fracturing, which is common for soils composed of glacial deposits overlying clayey till.…”
Section: The Role Of Preferential Flowmentioning
confidence: 79%